LEVEL OF SATISFACTION WITH SOCIO ECONOMIC PREFERENCES FOR NEIGHBOURHOOD QUALITY - Rahman, Norainah Abdul; Ali, Nor Eeda; Haron, Norhazlan; Abdullah, Kamariah (Jurnal Arsitektur dan Perencanaan (JUARA), 2020)
Level of satisfaction (LOS) is widely used by many studies in evaluating the current situation or provision of any services. For this study the level of satisafaction is focusing on socio economic preferences in evaluating the neighbourhood facilities and services for neighbourhood quality. This paper is continuation from pervious paper on neighbourhood quality. There are two variables used for socio economic background used are which are monthly income and home ownership. The key target of the study is assess the level of satisfaction of neighbourhood facilities and services with different socio economic background. Self-administered questionnaire survey distributed at three neighbourhood area in Manjung District Perak Malaysia with the sample of 421 respondents. The analysis used to assess the level of satisfaction with different socio economic background with neighbourhood facilities and services are descriptive analysis and one-way ANOVA test. Basically the result shows that all neighbourhood facilities and services are moderate to less level of satisfaction by different socio economic background. Even though at moderate level below 4.00 scale, the result shows that the lower income gives better level of satisfaction (3.63) compared to the higher income a bit lower level of satisfaction (3.45). Nevertheless peoples who have different home ownership gives almost similar result with average moderate below 4.00 scale. People who stay at their own house scale at 3.53, who stay at rental house scale at 3.57 and other house scale ate 3.57. Based on the result the local authority the Manjung Municipal Council and related agencies must be take into account to upgrade and improve the neighbourhood facilities and services in their neighbourhood area. The feedbacks from the peoples are the best method to get the actual situation and exact facts.